The Activities of NKVD Forces of Rear Defence Fronts in Lithuania (1944–1945) - Starkauskas, Juozas (Genocidas ir rezistencija, 1997)
This is an article on the NKVD army of the 3rd Belarusian background front and is a fragment of a paper on those Soviet military occupying forces (rifle regiments, border regiments and detachments, destruction battalions made up of collaborators) that fought against our partisans during the partisan war (1944–1953) and established the occupiers’ power in Lithuania